Metabolic challenges and key players in serpentinite-hosted microbial ecosystems - Popall, Rabja Maria; Postec, Anne; Lecoeuvre, Aurélien; Quéméneur, Marianne; Erauso, Gaël (Frontiers in Microbiology, 2023)
Serpentinite-hosted systems are amongst the most challenging environments for life on Earth. Serpentinization, a geochemical alteration of exposed ultramafic rock, produces hydrothermal fluids enriched in abiotically derived hydrogen (H2), methane (CH4), and small organic molecules. The hyperalkaline pH of these fluids poses a great challenge for metabolic energy and nutrient acquisition, curbing the cellular membrane potential and limiting electron acceptor, carbon, and phosphorous availability. Nevertheless, serpentinization supports the growth of diverse microbial communities whose metabolic make-up might shed light on the beginning of life on Earth and potentially elsewhere. Here, we outline current hypotheses on metabolic energy production, carbon fixation, and nutrient acquisition in serpentinizing environments. A taxonomic survey is performed for each important metabolic function, highlighting potential key players such as H2 and CH4 cycling Serpentinimonas, Hydrogenophaga, Methanobacteriales, Methanosarcinales, and novel candidate phyla. Methodological biases of the available data and future approaches are discussed.